2012
DOI: 10.1515/hf.2011.116
|View full text |Cite
|
Sign up to set email alerts
|

Comparative termite resistance of 12 Malaysian timber species in laboratory tests

Abstract: The effect of wood density and extractive compounds on heartwood durability against subterranean termites was studied. Twelve species of Malaysian hardwoods were tested against Coptotermes curvignathus and C. gestroi using a standard laboratory method. The results indicated that amount of extractive content is related to Malaysian hardwood termite durability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Timber species that possess higher extractive content and density displayed superior durability. Kadir and Hale [115] compared the resistance of twelve Malaysian timber species against subterranean termites and observed that the durability of the timbers varied according to their extractive content and density. Digestions of lignocellulose by termites were interfered by the antioxidants substances contained in wood extractives and, consequently, the termites have learnt to avoid wood that possesses a certain amount of the antioxidant compounds [116].…”
Section: Durability Against Biodeterioration Agentsmentioning
confidence: 99%
“…Timber species that possess higher extractive content and density displayed superior durability. Kadir and Hale [115] compared the resistance of twelve Malaysian timber species against subterranean termites and observed that the durability of the timbers varied according to their extractive content and density. Digestions of lignocellulose by termites were interfered by the antioxidants substances contained in wood extractives and, consequently, the termites have learnt to avoid wood that possesses a certain amount of the antioxidant compounds [116].…”
Section: Durability Against Biodeterioration Agentsmentioning
confidence: 99%
“…Our results were higher than those cited by Santana et al [24] for other older clones in Brazil. Other researchers obtained basic densities from 0.560 to 0.650 g cm -3 for rubberwood in Asian countries [3,[25][26][27][28].…”
Section: Resultsmentioning
confidence: 99%
“…When termite foragers encountered knots, the direction of excavation was changed to the less dense regions surrounding the hard density knots (Fengel and Wegener 1983). Several studies (Rust and Reierson 1977;Sajap and Sahri 1983;Mburu et al 2007;Ragon et al 2008;Little et al 2010;Kadir and Hale 2012;Kadir et al 2014;Ninomiya et al 2014) suggest that termite resistance (and natural durability) is mainly due to the extractive content and, additionally, the content and chemistry of lignin (Ohmura et al 1999;Wong et al 2005;Judd and Corbin 2009). The reaction wood is due to the external forces on young trees, such as fast blowing wind, which causes the compression of tissues.…”
Section: Wood Consumption Volume (Wcv) and Rate (Wcr)mentioning
confidence: 99%